Effect of Vitamin C on Clinical Outcomes of Critically Ill Patients With COVID-19: An Observational Study and Subsequent Meta-Analysis - Gavrielatou, Evdokia; Xourgia, Eleni; Xixi, Nikoleta A.; Mantelou, Athina G.; Ischaki, Eleni; Kanavou, Aggeliki; Zervakis, Dimitris; Routsi, Christina; Kotanidou, Anastasia; Siempos, Ilias I. (Frontiers in Medicine, 2022)
Background: Whether vitamin C provides any benefit when administered in critically ill patients, including those with coronavirus disease (COVID-19), is controversial. We endeavored to estimate the effect of administration of vitamin C on clinical outcomes of critically ill patients with COVID-19 by performing an observational study and subsequent meta-analysis. Methods: Firstly, we conducted an observational study of critically ill patients with laboratory-confirmed COVID-19 who consecutively underwent invasive mechanical ventilation in an academic intensive care unit (ICU) during the second pandemic wave. We compared all-cause mortality of patients receiving vitamin C (“vitamin C” group) or not (“control” group) on top of standard-of-care. Subsequently, we systematically searched PubMed and CENTRAL for relevant studies, which reported on all-cause mortality (primary outcome) and/or morbidity of critically ill patients with COVID-19 receiving vitamin C or not treatment. Pooled risk ratio (RR) and 95% confidence intervals (CI) were calculated using a random effects model. The meta-analysis was registered with PROSPERO. Results: In the observational study, baseline characteristics were comparable between the two groups. Mortality was 20.0% (2/10) in the vitamin C group versus 47.6% (49/103; p=0.11) in the control group. Subsequently, the meta-analysis included 11 studies (6 observational; 5 randomized controlled trials) enrolling 1807 critically ill patients with COVID-19. Mortality of patients receiving vitamin C on top of standard-of-care was not lower than patients receiving standard-of-care alone (25.8% versus 34.7%; RR 0.85, 95% CI 0.57–1.26; p=0.42). Conclusions: After combining results of our observational cohort with those of relevant studies into a meta-analysis of data from 1807 patients, we found that administration of vitamin C as opposed to standard-of-care alone might not be associated with lower mortality among critically ill patients with COVID-19. Additional evidence is anticipated from relevant large randomized controlled trials which are currently underway.